Synthesis, photophysics and biomolecule interactive studies of new hybrid benzo-2, 1, 3-thiadiazoles. (30th January 2020) - Neto, José S. S.; Krüger, Roberta; Balaguez, Renata A.; Fronza, Mariana G.; Acunha, Thiago V.; Oliboni, Robson S.; Savegnago, Lucielli; Iglesias, Bernardo A.; Alves, Diego
Abstract : New hybrid molecules containing benzo-2, 1, 3-thiadiazole, benzofuran and arylselanyl moieties were synthesized and their photophysics and biomolecule interactive studies were performed. Abstract : Four new hybrid molecules containing benzo-2, 1, 3-thiadiazole, benzofuran and arylselanyl moieties, named 4, 7-bis(3-(arylselanyl)benzofuran-2-yl)benzo[ c ][1, 2, 5]thiadiazoles, were designed and synthesized in good yields through an electrophilic cyclization of 4, 7-bis((2-methoxyphenyl)ethynyl)benzo[ c ][1, 2, 5]thiadiazole 1 and diaryl diselenides 2 using trichloroisocyanuric acid to generate electrophilic arylselanyl species. The photophysical properties of compounds 3a–d were investigated using UV-vis absorption and emission fluorescence analysis. The emission fluorescence analysis showed a yellow-orange region emission. Large Stokes shift values were observed for all new derivatives and attributed to the ICT state and to the electron-substituent properties. The biomolecule-binding DNA and HSA-binding interactions were also investigated by experimental and theoretical methods.